PARTIAL MELTING AND THE FORMATION OF GRANULITE FACIES ASSEMBLAGES IN NAMAQUALAND, SOUTH-AFRICA - Waters, D (1988)
Granulite facies metapelite, biotite gneiss and metabasic gneiss in Namaqualand contain coarse-grained, discordant, unfoliated, anhydrous segregations, surrounded by a finer grained, foliated matrix that commonly includes hydrous minerals. The segregations have modes consistent with the hypothesis that they are the solid and liquid products of the dehydration-melting reactions; Bt + Sil + Qtz + Pl = Grt ± Crd + Kfs + L (metapelite), Bt + Qtz + Pl = Opx + Kfs + L (biotite gneiss), and Hbl + Qtz = Opx + Cpx + Pl + L (metabasic gneiss). The size, shape, distribution and modes of segregations suggest only limited migration and extraction of melt. Growth of anhydrous poikiloblasts in matrix regions, development of anhydrous haloes around segregations and formation of dehydrated margins on metabasic layers enclosed in migmatitic metapelites all imply local gradients in water activity. Also, they suggest that individual segregations and bodies of partially melted rock acted as sinks for soluble volatiles. The preservation of anhydrous assemblages and the restricted distribution of late hydrous minerals suggest that retrograde reaction between hydrous melt and solids did not occur and that H2O in the melt was released as vapour on crystallization. -from Author